Drying behavior for Ocimum basilicumLamiaceae with the new system: exergy analysis and RSM modeling - Demirpolat, Ahmet B.; Aydogmus, Ercan; Arslanoglu, Hasan (Springer Heidelberg, 2022)
In this study, drying kinetics of Arapgir purple basil leaves under the isothermal and non-isothermal conditions have been investigated. Effective methods were evaluated by drying freshly collected basil leaves in the sun, isothermal, and non-isothermal systems. Energy efficiency was compared in different drying processes by performing exergy analysis in the drying process. It has been observed that the energy consumed and lost especially in the convection drying system (tray dryer) is very high. In the experiments performed in the PID (proportional integral derivative) system, the lowest efficiency was found in the isothermal process. Accordingly, the most suitable system in exergy efficiency was determined as the non-isothermal PID system. Maximum energy loss and minimum exergy efficiency were found at 45 degrees C temperature and 3.0 m/s airflow rate in the convection drying process. Exergy efficiencies were found to be approximately 4% in the convection tray dryer, 26% in the PID system under isothermal conditions, and 32% in the PID system under non-isothermal conditions. Optimization parameters in the drying process were determined by the response surface methodology (RSM), and the kinetic models were compared with the help of statistical analyses in the experiments. Midilli and Kucuk model has been found as the most compatible kinetic equation with the experimental data. According to this model results, correlation coefficient (R-2 > 0.990), sum of squared error (SSE<0.005), chi-square (chi(2)<1 center dot 10(-5)), and root mean square error (RMSE<0.003) values have been evaluated.
Keywords: Arapgir basil; Exergy analysis; Drying kinetics; RSM; Shrinkage modeling